REAKSI KOREA UTARA TERHADAP KEBIJAKAN KOREA SELATAN MEMBERHENTIKAN BANTUAN EKONOMI TERHADAP KOREA UTARA (2008-2011) - R. G. S. MOREN; Tri Joko Waluyo (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
This research explain about the relationship between South Korea and North Korea, describes the relationship between Korean leadership since Lee Myung Bak. Indeed, the relationship between the two Korean is not yet reconciled, they’re just only signed a truce agreement in 1953. A trigger disintegration of ideological differences between Korean are utilized by many foreigners, include US.This study experienced the problems when searching for concrete data about north korea, it’s because North Korea is a closed country that make it very difficult to access and also north korea alienate themselves from outsiders, as well as its nuclear holdings. Assisted by several books, journals, various kinds of articles and papers then I can finish this research.keywords: policy, economic aid, nuclear weapons